Organic Molecules in Interstellar Space: Latest Advances - Guélin, Michel; Cernicharo, Jose (Frontiers in Astronomy and Space Sciences, 2022)
Owing to their exceptional sensitivity and spectral resolution, the giant mm/sub-mm telescopes and interferometers allow to unambiguously detect and identify molecular species in nearby circumstellar clouds, interstellar nebulae and up to the most remote galaxies and quasars. The trace of prebiotic molecules will be followed along that path, with special emphasis on a cold dark cloud, located at 400 light-years from the Sun, a spiral galaxy at 6 Giga l-y and a quasar at {\bf 11} Giga l-y.